NADZAR AS AN EFFORT TO GAIN PROFIT AND ITS IDEAL IMPLEMENTATION IN AL-QARDH FINANCING IN ISLAMIC FINANCIAL INSTITUTIONS - Parmujianto, Parmujianto; Musataklima, Musataklima (Jurisdictie: Jurnal Hukum dan Syariah, 2025)
Qardh, or interest-free lending, is one of the financial instruments employed by Islamic Financial Institutions (IFIs). However, in contemporary practice, a phenomenon has emerged involving the use of the nadzar (vow) concept as a means of gaining profit, fundamentally contradicting the intrinsic nature of al-Qardh. This study examines the integration between al-Qardh and nadzar, its legal foundation, juridical consequences, and an ideal model of implementation within IFI practices. The research employs an empirical legal method with a sociological approach, collecting primary data through interviews with informants and relevant stakeholders and secondary data through document and literature studies. All data were analysed using a qualitative-descriptive approach. The findings indicate that nadzar can be voluntarily and temporarily combined within the al-Qardh scheme based on interpretations of the DSN-MUI fatwa that permits non-binding profit arrangements. Although nadzar is not legally binding, it holds a morally binding force as a religious commitment from the customer. Ideally, this model should be applied to productive rather than consumptive financing, with returns contingent upon the success of the financed venture rather than the mere disbursement of funds. This study offers practical contributions to the development of innovative and Sharia-compliant financing schemes while also enriching the theoretical discourse on legal engineering in Islamic economics. Qardh, atau pinjaman tanpa bunga, merupakan salah satu instrumen keuangan yang digunakan oleh Lembaga Keuangan Islam (LKI). Namun, dalam praktik kontemporer, muncul fenomena penggunaan konsep nadzar (janji) sebagai sarana untuk memperoleh keuntungan, yang secara fundamental bertentangan dengan sifat intrinsik al-Qardh. Penelitian ini mengkaji integrasi antara al-Qardh dan nadzar, landasan hukumnya, konsekuensi yuridisnya, serta model ideal implementasinya dalam praktik IFI. Penelitian ini menggunakan metode hukum empiris dengan pendekatan sosiologis, mengumpulkan data primer melalui wawancara dengan informan dan pemangku kepentingan terkait, serta data sekunder melalui studi dokumen dan literatur. Semua data dianalisis menggunakan pendekatan kualitatif-deskriptif. Temuan menunjukkan bahwa nadzar dapat secara sukarela dan sementara diintegrasikan dalam skema al-Qardh berdasarkan interpretasi fatwa DSN-MUI yang memperbolehkan pengaturan keuntungan yang tidak mengikat. Meskipun nadzar tidak mengikat secara hukum, ia memiliki kekuatan mengikat secara moral sebagai komitmen agama dari pelanggan. Idealnya, model ini harus diterapkan pada pembiayaan produktif daripada konsumtif, dengan pengembalian bergantung pada kesuksesan usaha yang dibiayai daripada sekadar pencairan dana. Studi ini memberikan kontribusi praktis bagi pengembangan skema pembiayaan inovatif dan sesuai syariah, sekaligus memperkaya diskursus teoretis tentang rekayasa hukum dalam ekonomi Islam.